Performance of Split Air Conditioner with Capillary Pipe Variations with R32 Refrigerant on Ships - Urip Prayogi; Frengki Mohammad Felayati; M. Ilham Bintang H (International Journal of Marine Engineering Innovation and Research, 2024)
The hot temperature on the ship will interfere with the comfort of the crew, so an air conditioning machine is needed to cool down. Hot conditions make air conditioning needed on the ship as a means of cooling when the ship sails. Split AC performance is very necessary so that the temperature released remains optimal. Split air conditioners have many components, for example, capillary pipes, capillary pipes play a very important role in obtaining low temperatures. Therefore, it is necessary to research variations in the length and diameter of capillary pipes. As a pressure-lowering device and regulating the amount of refrigerant liquid flowing, the length and diameter of capillary pipes greatly affect the cooling process. If you find the right and right variation, you will get a temperature lower than the standard Therefore, to get extra cooling for split air conditioners, research is proposed on the effect of variations in the length of capillary pipes on the work performance of split air conditioner machines using R32 refrigerant for ship accommodation room. To know the effect of cooling more extra because with changes in capillary pipes further maximize cold temperatures by using additional capillary pipe length. This study uses an experimental method with a split air conditioner 0.5 Hp as the main object and variations in capillary pipe length. the temperature after the capillary pipe is varied is lower than the standard, namely the standard achievement of 55.9 for a variation of 72 cm, which is 26.4, and the last variation of 159 cm, which is 29.